Cancer cells suppress NK cell activity by actin-driven polarization of inhibitory ligands to the immunological synapse - Céline Hoffmann; Liza Filali; Hannah Wurzer; Diogo Pereira Fernandes; Takouhie Mgrditchian; Wanxin Huang; Flora Moreau; Max Krecké; Clément Thomas (Proceedings of the National Academy of Sciences, 2025)
Natural killer (NK) cells engage target cells via the immunological synapse (IS), where inhibitory and activating signals determine whether NK cell cytotoxicity is suppressed or activated. We previously reported that cancer cells can rapidly remodel their actin cytoskeleton upon NK cell engagement, leading to F-actin accumulation at the synapse. Here, we show that this process inhibits NK cell activation as indicated by impaired MTOC and lytic granule polarization. Exploring the underlying mechanism, we demonstrate that actin remodeling drives the recruitment of inhibitory ligands, such as HLA-A, -B, and -C, to the synapse. Disrupting HLA interaction with their cognate inhibitory receptors KIRs restores NK cell activation. Using NK cells expressing inhibitory KIR receptors, matched or unmatched to HLA molecules on cancer cells, we show that synaptic F-actin accumulation and matching KIR–HLA interactions jointly suppress NK cell cytotoxicity. Our findings reveal an immune evasion strategy in which cancer cells impair NK cell activation by altering synaptic signaling through actin cytoskeleton–driven recruitment of inhibitory signals to the IS.